Analisis Sistem Informasi Pengaduan Masyarakat Berbasis Web Menggunakan Metode Agile - Siti Khodijah; Winona Septi Aulia (Journal of Information Systems and Business Technology, 2025)
The public complaint system plays an important role in improving the quality of public services, especially in government institutions such as the DPR RI Building. This study aims to design and test a web-based complaint information system with a software development method using the Agile approach. System development is carried out through several sprint stages, including identifying needs, creating features, and testing the system. The type of testing used is Black Box Testing, focusing on key features such as login, dashboard, navigation menu, data management, and form validation. The test results show that all features run as expected, and this system can manage complaints in an efficient, transparent, and orderly manner. Therefore, this system is declared successful in improving the efficiency of complaint handling in the DPR RI environment.